2014
DOI: 10.1093/humrep/deu182
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone: correlation with testosterone and oligo- or amenorrhoea in female adolescence in a population-based cohort study

Abstract: STUDY QUESTIONSCan serum anti-Müllerian hormone (AMH) levels measured in female adolescents predict polycystic ovary syndrome (PCOS)-associated features in adolescence and early adulthood?SUMMARY ANSWERAMH levels associated well with PCOS-associated features (such as testosterone levels and oligoamenorrhoea) in adolescence, but was not an ideal marker to predict PCOS-associated features in early adulthood.WHAT IS KNOWN ALREADYSeveral studies have reported that there is a strong correlation between antral folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
6
29
0
3
Order By: Relevance
“…[37,40,42,43] pooled the results of all study subjects for the correlation of AMH with metabolic indices, which may have diluted any observed effect inherently related to the pathophysiology of PCOS. In all mentioned studies, AMH was shown to be elevated in women with PCOS compared to healthy controls [31,32,37,38], in correspondence with other literature [21].…”
Section: Metabolic Syndrome and Amh In The Case Of Pcossupporting
confidence: 81%
See 2 more Smart Citations
“…[37,40,42,43] pooled the results of all study subjects for the correlation of AMH with metabolic indices, which may have diluted any observed effect inherently related to the pathophysiology of PCOS. In all mentioned studies, AMH was shown to be elevated in women with PCOS compared to healthy controls [31,32,37,38], in correspondence with other literature [21].…”
Section: Metabolic Syndrome and Amh In The Case Of Pcossupporting
confidence: 81%
“…This was supported by another study among adolescents [31], including subjects with a diagnosis of PCOS (5.3%). In this study, AMH was not related to any metabolic parameters [31]. When researching the degree of insulin resistance or level of fasting insulin alone in relation to AMH, a significant correlation was found by two studies [32,33], whereas another study was not able to confirm this correlation [34].…”
Section: Relationship Of Amh With Metabolic Parameterssupporting
confidence: 64%
See 1 more Smart Citation
“…Some studies have shown that AMH closely correlated especially with testosterone (43,46), and others have shown that it correlated with D4-A and FAI (47). In our study, AMH was found to significantly correlate with androgens such as DHEAS, fT, D4-A.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone concentrations are also positively correlated with AMH levels (31, 32) and were controlled for in the current analysis. We did not measure estradiol levels since the blood draw was not timed to the menstrual cycle and premenopausal estradiol has a weaker association with breast cancer risk compared to postmenopausal levels (30, 33, 34).…”
Section: Discussionmentioning
confidence: 99%